Elimination of citrus tristeza virus and greening pathogens from exotic germplasm through in vitro shoot tip grafting in citrus*. - KUMAR, N VIJAYA; GHOSH, D K; DAS, A K; SINGH, AWTAR; SINGH, SHYAM (The Indian Journal of Agricultural Sciences, 2011)
A laboratory experiment was conducted during 2002-04 to establish different introduced/exotic citrus scion cultivars through in vitro grafting in quarantine greenhouse and to generate the'clean nucleus stock of diverse citrus germplasm to strengthen the citrus gene bank which will be helpful for both commercial and scientific purpose. The grafting success was maximum in 'Ruby Blood Orange' (80.00%) followed by 'Dhakula Local mandarin' (66.66%) and 'Caffin Clementine' (66.67%).The trans grafting success was maximum 80% in 'Campbell Valencia', 'Dhakula local mandarin' and Caffin Clementine.The percentage ofshoot tips grafted citrus exotic germplasm tested negative for citrus tristeza virus and greening bacterium are 76 and 86.95% respectively.